Proyecto de musealización de los restos hallados en la estación de Ópera (Metro de Madrid). Reconstrucciones infográficas, escaneo laser 3D y digitalización del patrimonio arqueológico. - Eduardo Penedo Cobo; Patricia Moraga Vaz; Elia Organista Labrado; Áurea Izquierdo Zamora; Ana Belén Martínez Granero (Virtual Archaeology Review)
In 2009, the archaeological and paleontological investigation associated with the new lift installation project in Opera Underground Station in Madrid, revealed remains of the ancient town structure of the lost Caños del Peral Square ( XVI-XVII and XVIII centuries), currently known as Isabel II Square. The recovery of these remains, which are of immense historical heritage value since they are significant elements of Madrid’s past, has led to the creation of a museum space in the station itself. In the explanatory document a range of techniques have been used including graphic information, animation and 3D imagery of the elements recorded during the excavation.